Low‐dose hydrocortisone in patients with COVID‐19 and severe hypoxia: The COVID STEROID randomised, placebo‐controlled trial. Issue 10 (20th September 2021) - Munch, Marie Warrer; Meyhoff, Tine Sylvest; Helleberg, Marie; Kjær, Maj‐Brit Nørregaard; Granholm, Anders; Hjortsø, Carl Johan Steensen; Jensen, Thomas Steen; Møller, Morten Hylander; Hjortrup, Peter Buhl; Wetterslev, Mik; Vesterlund, Gitte Kingo; Russell, Lene; et al.
Abstract : Background: In the early phase of the pandemic, some guidelines recommended the use of corticosteroids for critically ill patients with COVID‐19, whereas others recommended against the use despite lack of firm evidence of either benefit or harm. In the COVID STEROID trial, we aimed to assess the effects of low‐dose hydrocortisone on patient‐centred outcomes in adults with COVID‐19 and severe hypoxia. Methods: In this multicentre, parallel‐group, placebo‐controlled, blinded, centrally randomised, stratified clinical trial, we randomly assigned adults with confirmed COVID‐19 and severe hypoxia (use of mechanical ventilation or supplementary oxygen with a flow of at least 10 L/min) to either hydrocortisone (200 mg/d) vs a matching placebo for 7 days or until hospital discharge. The primary outcome was the number of days alive without life support at day 28 after randomisation. Results: The trial was terminated early when 30 out of 1000 participants had been enrolled because of external evidence indicating benefit from corticosteroids in severe COVID‐19. At day 28, the median number of days alive without life support in the hydrocortisone vs placebo group were 7 vs 10 (adjusted mean difference: −1.1 days, 95% CI −9.5 to 7.3, P  = .79); mortality was 6/16 vs 2/14; and the number of serious adverse reactions 1/16 vs 0/14. Conclusions: In this trial of adults with COVID‐19 and severe hypoxia, we were unable to provide precise estimates of the benefits and harms of hydrocortisone as compared with placebo as only 3% of the planned sample size were enrolled. Trial registration : ClinicalTrials.gov: NCT04348305. European Union Drug Regulation Authorities Clinical Trials (EudraCT) Database: 2020‐001395‐15.